Development of the elderly-constipation impact scale (e-cis) to measure quality of life (QoL) in the elderly with chronic constipation - Abdul Wahab, Patimah; Lee, Yeong Yeh; Ali, Siti Hawa; Abdul Kadir, Azidah; Mohd Yusof, Danah (2018)
Chronic constipation is a common symptom-based disorder among the elderly. It may affect the quality of life (QoL). However, due to a lack of questionnaire that focuses on the elderly group, this effect is not well understood. This study aimed to develop the Elderly-Constipation Impact Scale (E-CIS) to measure constipation-specific QoL in the elderly with chronic constipation. A pool of items was generated from the findings of the qualitative study, literature review, and expert review. A total of 268 elderly, who experience chronic constipation, from community setting of Kelantan and Terengganu participated in the study to evaluate its reliability and validity: 46 elderly involved in the qualitative study to generate the items, 22 elderly participated in debriefing interview to refine the scale and 200 elderly involved in a cross-sectional study to reduce the items and to determine the scale’s structure. The finding revealed that exploratory factor analysis (EFA) reduced the 40-item scale to 27-item E-CIS. The items were grouped into eight subscales: “daily activities”, “treatment satisfaction”, “lack of control of bodily function”, “diet restriction”, “symptom intensity”, “anxiety”, “dietary fibre intake” and “fluid intake”. The E-CIS showed high internal consistency (Cronbach’s alpha = 0.80). In conclusion, the finding of this study supports the reliability and validity of the E-CIS to assess the impact of chronic constipation on the elderly’s QoL. However, further validation is needed to determine the extent of items in the scale reflecting its construct to measure constipation-QoL in the elderly with chronic constipation.